Value of early weight measurements as predictors of body weight at later ages in reindeer - C.J. Petersson; B. Danell (Rangifer, 1993)
Phenotypic variances in live weight in a reindeer population and repeatabilities of the weights were estimated. The population consisted of 1847 and 1878 unselected male and female calves respectively, for which data from weighings at 2 and 7 months of age were available. All individuals in a selected population, consisting of 469 of the heaviest females, were weighed at 2, 7 and 19 months of age. The data were colleted during four successive years, 1986 - 1989. An indirect selection model for improving female weight at 19 months of age was proposed. Variance in the unselected population was higher between animals than within animals. Repeatability was estimated to be 0.636 for the male calves and 0.609 for the female calves. In the selected population, within-individual variance was higher than between-animal variance. Repeatabilities were, after correction for the effect of selection, 0.316 (between 2 and 19 months) and 0.548 (between 7 and 19 months). The aim of the selection model was to increase the average weight in the primiparous group to improve their calf production ability. Using the model, the number of animals weighing equal to or more than a certain threshold weight and the number needed for recruitment at 19 months of age could be determined.